2014
DOI: 10.1080/10228195.2014.958519
|View full text |Cite
|
Sign up to set email alerts
|

Entry-level students’ reading abilities and what these abilities might mean for academic readiness

Abstract: The National Benchmark Tests Project (NBTP) was commissioned by Higher Education South Africa and became operational in 2009. One of the main aims of the NBTP is to assess the extent to which entry-level students might be said to be ready to cope with the conventional demands of academic study in three key areas: academic literacy; quantitative literacy; and mathematics. This paper presents an analysis of the academic literacy readiness of a sample of registered students as reflected in their performance on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…These findings confirm and augment those reported by Cliff and Hanslo (2009) Fleisch, Schöer and Cliff 2015). Furthermore, studies have also shown that school-leavers embarking on university studies are generally inadequately prepared to cope with the language-of-instruction demands of studies in higher education (Ramukumba and Gravett 2004;Cliff 2014 and2015).…”
Section: Resultsmentioning
confidence: 99%
“…These findings confirm and augment those reported by Cliff and Hanslo (2009) Fleisch, Schöer and Cliff 2015). Furthermore, studies have also shown that school-leavers embarking on university studies are generally inadequately prepared to cope with the language-of-instruction demands of studies in higher education (Ramukumba and Gravett 2004;Cliff 2014 and2015).…”
Section: Resultsmentioning
confidence: 99%
“…So in language testing and course design, we depend on the construct of the language ability which is the focus of these interventions. In respect of academic language ability, this paper refers cursorily only to the latest rationale, but its history and how it was arrived at are discussed at length elsewhere Weideman 2013a, 2013b;Weideman, Patterson and Pot 2016;Cliff 2014Cliff , 2015; the paradigmatic origins of this in the work of sociolinguists such as Hymes (1972), Habermas (1970) and Halliday (1978) have also been noted in more detail in Weideman, Du Plessis and Steyn (2017).…”
Section: The Critical Importance Of a Theoretically Defensible Definimentioning
confidence: 99%
“…(Fleisch et al 2015: 167) Not only did Fleisch et al's (2015) study reveal that English FAL school-leavers perform poorly overall on the NBT AL when compared to their HL counterparts, it also showed that this too was the case at the level of the subdomains of academic literacy that constitute the construct of academic literacy as defined for this test. These subdomains include students' ability to recognise/understand/use cohesion, communicative function, essential versus non-essential information, grammar (syntax), inferencing, metaphorical expressions, discourse relations, text genre, and vocabulary (see Cliff and Yeld 2006;Cliff 2014Cliff , 2015. With regard to differential performance between the two groups on the ability to work out the meaning of vocabulary in context, Fleisch et al (2015: 170) found that the gap for the students whose marks in English HL and FAL were around 60% was less than .5 of the standard deviation, but that this gap widened as these marks increased.…”
Section: Literature Reviewmentioning
confidence: 99%